2019
DOI: 10.1111/apm.12993
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus citriodora leaf extract‐mediated biosynthesis of silver nanoparticles: broad antimicrobial spectrum and mechanisms of action against hospital‐acquired pathogens

Abstract: Pathogen resistance to conventional antibiotics has become a serious clinical and public health problem, making the development of an alternative mean a very urgent issue. Recently, biosynthesis of silver nanoparticles (AgNPs) was successfully accomplished in the presence of Eucalyptus citriodora leaf extract as a reducing agent. In this study, the antimicrobial mechanisms of AgNPs against important hospital‐acquired pathogens, including Gram‐positive, Gram‐negative bacteria, and fungi were further assessed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…The MIC and MFC ranged from 0.25 to 0.5 µg/ml and 0.5 to 1 µg/ml, respectively. A similar anti‐candidal activity of AgNPs synthesized from another species of Eucalyptus has been reported in our earlier work (Paosen et al, 2019). It is to be noted that E. camaldulensis is the most widespread species of eucalyptus and abundant of the leaf litters are available from paper manufacturers (Siramon et al, 2009).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The MIC and MFC ranged from 0.25 to 0.5 µg/ml and 0.5 to 1 µg/ml, respectively. A similar anti‐candidal activity of AgNPs synthesized from another species of Eucalyptus has been reported in our earlier work (Paosen et al, 2019). It is to be noted that E. camaldulensis is the most widespread species of eucalyptus and abundant of the leaf litters are available from paper manufacturers (Siramon et al, 2009).…”
Section: Resultssupporting
confidence: 89%
“…The surface morphological changes in the yeast cells may indicate the interaction of bio‐AgNPs with the cell wall and cell membrane. Bio‐AgNPs from E. citriodora leaf extract inhibited biofilms in C. albicans due to the alteration of membrane surface charges of pathogenic fungi following the exposure to the nanoparticles, leading to membrane disruption (Paosen et al, 2019). The release of Ag + from AgNPs was demonstrated to react with the thiol group of protein portion, generally presented in microbial enzymes, such as glyceraldehyde‐3‐phosphate dehydrogenase and malate dehydrogenase, resulting in pathogen inactivation (Jiang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Eucalyptus camaldulensis leaves contain a wide range of bioactive compounds including saponins, tannins, flavonoids, carbohydrate and proteins [ 28 ], which play important roles as reducing and capping agent during the formation of nanoparticles [ 29 , 30 ]. There are many articles published on the synthesis of AgNPs using different species of Eucalyptus such as Eucalyptus corymbia [ 31 ], Eucalyptus globules [ 32 ], Eucalyptus critriodora [ 33 ], and Eucalyptus tereticornis [ 34 ] etc… But, few studies have been reported in the using of aqueous extract of Eucalyptus camaldulensis leaves for synthesis silver nanoparticles [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus citriodora belongs to the Myrtaceae family, and these species are known for the characteristics of their essential oils. It is known that the E. citriodora essential oil (ECEO) has a wide spectrum of biological activities, including herbicidal [3,4] , antifungal [5] , insecticide [6] , antioxidant [7,8] , antimicrobial [9,10] properties. However, the storage of EOs is a critical matter due to their sensitivity to heat, humidity and air, being subject to hydrolysis, oxidation, dehydration and isomerization reactions [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%